2022
DOI: 10.1093/brain/awac326
|View full text |Cite
|
Sign up to set email alerts
|

PTPA variants and impaired PP2A activity in early-onset parkinsonism with intellectual disability

Abstract: The protein phosphatase 2A complex (PP2A), the major Ser/Thr phosphatase in the brain, is involved in a number of signaling pathways and functions, including the regulation of crucial proteins for neurodegeneration, such as alpha-synuclein, tau, and LRRK2. Here, we report the identification of variants in the PTPA/PPP2R4 gene, encoding a major PP2A activator, in two families with early-onset parkinsonism and intellectual disability. We carried out clinical studies and genetic analyses, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 112 publications
0
14
0
Order By: Relevance
“…To further explore the effect of the variant p.-Met329Val on the expression of PTPA, we assessed RNA and protein levels via Western blotting and RT-qPCR by overexpressing wild-type PTPA (PTPA WT ) and p.Met329Val PTPA (PTPA M329V ) as previously reported. 5 We found a significant reduction in protein levels in cells expressing PTPA M329V compared with PTPA WT , while no significant difference in PTPA mRNA expression was observed (Fig. 2A-C).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…To further explore the effect of the variant p.-Met329Val on the expression of PTPA, we assessed RNA and protein levels via Western blotting and RT-qPCR by overexpressing wild-type PTPA (PTPA WT ) and p.Met329Val PTPA (PTPA M329V ) as previously reported. 5 We found a significant reduction in protein levels in cells expressing PTPA M329V compared with PTPA WT , while no significant difference in PTPA mRNA expression was observed (Fig. 2A-C).…”
Section: Resultsmentioning
confidence: 67%
“…Recently, two homozygous variants (p.Met298Arg, p.Ala171Asp) in PTPA ( protein phosphatase 2A ) were identified as the disease cause in two pedigrees of African descent 5 . The patients had early‐onset parkinsonism and intellectual disability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many Whole Exome Sequencing projects have been recently conducted in large cohorts of patients but have resulted in very few novel PD-causative genes. 27 These observations suggest either the possibility of an incomplete detection of variants in already known PD genes using conventional molecular approaches, or the existence of other still-unknown genetic factors, possibly acting in a multifactorial model to influence PD susceptibility even in patients with early onset of the disease. 28,29 It is expected that large ongoing projects on PD genetics, such as the worldwide GP2 effort (Global Parkinson's Genetic Project; https://gp2.org), will eventually address this major unsolved issue.…”
Section: Discussionmentioning
confidence: 99%
“…Together, increased ROS production and αSyn aggregation accompanied by impaired autophagy create a vicious cycle that leads to neuronal cell death in Parkinson’s disease (PD). Moreover, decreased PP2A levels and activity have been implicated in the pathophysiology of Alzheimer’s disease and PD, , and a recent study identified point mutations in an endogenous PP2A activator, leading to reduced PP2A activity, proposed to contribute to early onset PD . Therefore, PP2A activating compounds could tackle several pathophysiological mechanisms in neurodegenerative diseases and eventually lead to a disease-modifying effect.…”
Section: Introductionmentioning
confidence: 99%